2018
DOI: 10.1093/jee/toy111
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Trapping Codling Moth, Cydia pomonella (Lepidopteran: Torticidae), Using a Kairomone Lure Reduces Fruit Damage in Commercial Apple Orchards

Abstract: Codling moth Cydia pomonella L. (Lepidoptera: Tortricidae) is a major pest of pome fruits worldwide. Fruit is damaged by larval feeding, and numbers of larvae are directly related to the numbers of females in the preceding generation. In Pacific Northwest, apple orchards, C. pomonella are generally managed with insecticides and mating disruption. However, additional control methods are needed when these treatments fail or are undesirable. Using a three-component kairomone lure that attracts both sexes, we mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Female codling moth comprised a high proportion (63%–80%) of total catch with this 4‐component lure in trials conducted throughout the 2018 season. The new 4‐component blend was found to be threefold more attractive compared to a blend composed of N‐butyl sulphide, PE and AA (Landolt et al, ) that has been used effectively to mass trap codling moth (Jaffe et al, ). Ternary blends with one of any of the four components subtracted caught significantly fewer moths than the 4‐component blend.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Female codling moth comprised a high proportion (63%–80%) of total catch with this 4‐component lure in trials conducted throughout the 2018 season. The new 4‐component blend was found to be threefold more attractive compared to a blend composed of N‐butyl sulphide, PE and AA (Landolt et al, ) that has been used effectively to mass trap codling moth (Jaffe et al, ). Ternary blends with one of any of the four components subtracted caught significantly fewer moths than the 4‐component blend.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, extensive field testing in North America and South America found no evidence that N‐butyl sulphide increased attraction of PE + AA (Basoalto, Mujica, Cichon, Fuentes‐Contreras, & Barros‐Parada, ). Nevertheless, mass trapping of codling moth with the N‐butyl sulphide plus PE + AA lures using 120 traps ha −1 significantly reduced levels of fruit injury in commercial orchards (Jaffe et al, ). The potential for mass trapping to manage codling moth effectively could be much greater if traps were baited with the 4‐component blend identified here because a much greater number of female moths would be removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study with mass trapping of codling moth in commercial apple orchards reduced fruit injury 50% using 124 traps/ha serviced every other week all season (Jaffe, Guedot, & Landolt, ). Knight, Mujica, et al, previously showed that a 4‐K lure caught 3.7‐fold more female codling moth than the lure used by Jaffe et al, ( n ‐butyl sulphide + PE +AA), suggesting that the efficacy of mass trapping could be significantly improved with the 4‐K lure and/or the cost of the programme may be reduced with the need for fewer traps.…”
Section: Discussionmentioning
confidence: 99%
“…Mass trapping techniques have been used to successively suppress the populations of various Lepidoptera pest species [8,[23][24][25]. This is the first study to investigate the field efficacy of mass trapping using sex pheromones for the reduction of both adult and larval male E. grisescens populations.…”
Section: Discussionmentioning
confidence: 99%